Design Considerations of Laser Source in a Ring Network Based on Fiber Distributed Data Interface (FDDI) - Abdullah, Sercote N.; Jawad, Hussein A.; Mohammed, Hussam A.; Mohammed, Hussam A. (Iraqi Journal of Laser, 2002)
This work presents the use of laser diode in the fiber distributed data interface FDDI networks. FDDI uses optical fiber as a transmission media. This solves the problems resulted from the EMI, and noise. In addition it increases the security of transmission. A network with a ring topology consists of three computers was designed and implemented. The timed token protocol was used to achieve and control the process of communication over the ring. Nonreturn to zero inversion (NRZI) modulation was carried out as a part of the physical (PHY) sublayer. The optical system consists of a laser diode with wavelength of 820 nm and 2.5 mW maximum output power as a source, optical fiber as a channel, and positive intrinsic negative (PIN) photodiode with maximum responsivity at wavelength of 820 nm as a detector. Practical tests were carried out on the laser diode showed that the output characteristics and spectral characteristics of the laser diode depend largely on the drive current. The maximum separation distance between successive stations in the ring was 5.4 km. From the performance tests, it was concluded that the maximum throughput and maximum access delay are directly proportional to length of the transmitted information. A trade off between the transmitted information length and the maximum access delay is needed.